Innokentij Ivanovich Tyzhnov as a translator of N. Witsen’s Siberian materials - T. N. Iljushechkina (Библиосфера)
The author investigates the translation from Dutch to Russian one of the «documents» on the conquest of Siberia by Ermak, published by N. Vitsen in his book «Noord en Oost Tartarye» (Amsterdam, 1705) and known today as the «The description of Siberia by Nikiphorus Venyukov». Considered are textual differences of the Dutch original and Russian translation made by I. I. Tyzhnovym. The role of I. I. Tyzhnov’s work for literary history «Siberia Description» is determined.